The role of climatic and bioclimatic conditions in the development of health tourism product - Didaskalou, E. A.; Nastos, P. T. (Anatolia, 2003)
The aim of this paper is to discuss the concept of health tourism product as a competitive tourism product with a focus on Ikaria Island, Greece. The diversification of the health tourism product is explored and the study identifies key components for a successful development of a spa resort. The paper also examines the prospects for the thermal/mineral springs of Ikaria Island, taking account of the climatic and bioclimatic regimes of the area. The study concludes that there are prospects for future development if the spa product is diversified. This, in combination with the good climatic conditions of the area, can be a starting point for providing services in order to satisfy potential clients. Β© 2003 anatolia Printed in Turkey. All rights reserved.
Keywords: bioclimatology; climate effect; Climatic and bio-climatic conditions; Eurasia; Europe; Greece; health services; Health tourism; Ikaria; Northern Aegean; Product diversification; Southern Europe; tourism development; tourist attraction